2021
DOI: 10.3138/cjhs.2021-0006
|View full text |Cite
|
Sign up to set email alerts
|

Understanding sexual and reproductive health needs of immigrant adolescents in Canada: A scoping review

Abstract: Despite the large number of immigrant adolescents in Canada, research on their knowledge of sexual and reproductive health and rights (SRHR) and information needs is nearly nonexistent. A scoping review was undertaken following the PRISMA-ScR statement to identify and assess the existing literature regarding SRHR needs of immigrant adolescents in Canada. Of the 1514 articles retrieved from our search strategy, 15 studies met our inclusion criteria. The results from our review identifies three unique themes rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Moreover, by encouraging a more direct, personal, and open line of communication with immigrant adolescents, the research team was able to learn of their relationship to research engagement more intimately. Our study was able to add to this small, but growing body of literature, particularly by ensuring a reflective attitude that aligns with the priorities of our target audience ( 31 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, by encouraging a more direct, personal, and open line of communication with immigrant adolescents, the research team was able to learn of their relationship to research engagement more intimately. Our study was able to add to this small, but growing body of literature, particularly by ensuring a reflective attitude that aligns with the priorities of our target audience ( 31 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the AAG members had indicated that they strongly agreed with the statement “I feel that the input provided through this activity will be considered by the organizers”. To create impact and change within a specific demographic group, it is imperative to utilize their advice and put it into action whenever possible; doing so encourages appropriate representation in subsequent policies and programs ( 30 , 31 ). Our study implies that future investigations would need to focus on applying this finding in order to develop accessible knowledge translation tools.…”
Section: Discussionmentioning
confidence: 99%
“…For immigrant adolescents, specific needs are warranted to achieve healthy behaviors that adequately navigate their cultural identities, migration contexts, family expectations, and emerging attitudes developed within the Canadian context ( 8 ). For example, in some cultures of immigrant populations, sensitive topics such as sexual and reproductive health (SRH) are rarely discussed during adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…To attain Canadian promises of inclusion and diversity, developing SRH resources and services specific to the adolescent immigrant population is paramount. In the absence of SRH resources and services that are inclusive of immigrant adolescents' needs, the young immigrant population in Canada may adopt unhealthy SRH attitudes and behaviors or experience exclusion and discrimination within SRH care ( 8 ). Despite these concerns, there is a lack of research on adolescent SRH needs from the perspective of immigrant adolescents within the Canadian context.…”
Section: Introductionmentioning
confidence: 99%